ECG Quiz no. 20 - Okreglicki, A (SA Heart Journal, 2017)
A 75-year old man was admitted having had syncope earlier that day and feeling unwell afterwards, but without chest pain. He had no past medical history and was on no medication. On admission his heart rate was 44bpm and BP 170/80. Blood chemistry was normal. A simple definitive procedure was done in the cardiac catheterisation laboratory. This ECG was done on arrival back in the cardiac ward after the cardiac procedure. He was now asymptomatic.